PENGARUH KESEMPATAN INVESTASI, LIKUIDITAS DAN PROFITABILITAS TERHADAP KEBIJAKAN DEVIDEN PT. UNITED TRACTORS TBK - Poni Yanita (LP2M Universitas Bina Bangsa, 2024)
This study aims to determine: 1) Is there an influence of Investment Opportunities on Dividend Policy at PT. United Taxors Tbk period 2012-2021. 2) Is there an effect of Liquidity on Dividend Policy at PT. United Taxors Tbk period 2012-2021. 3) Is there any influence Profitability on Dividend Policy at PT. United Taxors Tbk period 2012-2021. 4) Is there an influence of Investment Opportunity, Liquidity and Profitability on Dividend Policy at PT. United Taxors Tbk period 2012-2021. 5) How much influence does Investment Opportunity, Liquidity and Profitability have on Dividend Policy at PT. United Taxors Tbk period 2012-2021.This research was conducted at PT. United Tractors Tbk which is listed on the Indonesia Stock Exchange as a source for obtaining financial data with the website www.idn.financial.co.id. The analytical tool used is multiple linear analysis using SPSS version 20. Based on the results of the study, it shows that: 1) There is no significant influence between Investment Opportunities on Dividend Policy at PT. United Taxors Tbk period 2012-2021. 2) There is no significant influence between Liquidity on Dividend Policy at PT. United Taxors Tbk period 2012-2021. 3) There is no significant influence between Profitability on Dividend Policy at PT. United Taxors Tbk period 2012-2021. 4) There is no significant influence between Investment Opportunities, Liquidity and Profitability on Dividend Policy at PT. United Taxors Tbk period 2012-2021. 5) The magnitude of the influence of Investment Opportunities, Liquidity and profitability on Dividend Policy is 40.2% while the remaining 59.8%